Epidemiology, genetics and management of vitiligo in the USA: an All of Us investigation - Aditya K. Gupta; Vasiliki Economopoulos (Journal of Dermatological Treatment)
Background Vitiligo is an autoimmune skin depigmentation disorder significantly impacting quality of life. This condition is difficult to treat, with high relapse rates. Additionally, vitiligo associates with other autoimmune conditions, complicating patient management. Improving patient outcomes relies on understanding vitiligo’s clinical landscape and genetic risk factors.Objectives We aimed to understand vitiligo’s patient distribution, current management practices, how comorbid autoimmune conditions influence treatment and how genetic risk factors vary in diverse populations.Methods We conducted a cross-sectional study of the All of Us research program, consisting of surveys, electronic health records and genomic data from 206,173 participants in the USA recruited between the summer of 2017 and 1 July 2022. We determined diagnostic and prescribing rates and elucidated differences in genetic risk within different populations.Results Oral corticosteroids are most frequently prescribed, followed by other immunosuppressive drugs and topical medications. Comorbid systemic lupus erythematosus impacted treatment choices. Single nucleotide polymorphisms associated with increased risk in patients of European decent were not always associated with increase risk in patients of other ancestry.Conclusions This work highlights the current treatment landscape for vitiligo in the USA. We demonstrated that comorbid conditions impact treatment choices and genetic risk factors vary between ethnic groups.